Search for rare $B^0_{(s)}→ μ^+ μ^- μ^+ μ^-$ decays - collaboration, L; Aaij, R; Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; et al. (2013)
\noindent A search for the decays $B^0_{s}→ μ^+ μ^- μ^+ μ^-$ and $B^0 → μ^+ μ^- μ^+ μ^-$ is performed using data, corresponding to an integrated luminosity of 1.0\ensuremath{\{\,fb}^{-1}}\xspace, collected with the LHCb detector in 2011. The number of candidates observed is consistent with the expected background and, assuming phase-space models of the decays, limits on the branching fractions are set: \{${\ensuremath{\cal B}\xspace}(B^0_{s}→ μ^+ μ^- μ^+ μ^-) < 1.6 \ (1.2) × 10^{-8}$} and \{${\ensuremath{\cal B}\xspace}(B^0 → μ^+ μ^- μ^+ μ^-)< 6.6 \ (5.3) × 10^{-9}$} at 95\,% (90\,%) confidence level. In addition, limits are set in the context of a supersymmetric model which allows for the $B^0_{(s)}$ meson to decay into a scalar ($S$) and pseudoscalar particle ($P$), where $S$ and $P$ have masses of 2.5 GeV and 214.3 MeV, respectively, both resonances decay into $μ^+μ^-$. The branching fraction limits for these decays are \{${\ensuremath{\cal B}\xspace}(\ensuremath{B^0_{s}→ SP}\xspace) < 1.6 \ (1.2) × 10^{-8}$} and \{${\ensuremath{\cal B}\xspace}(\ensuremath{B^0→ SP}\xspace)< 6.3 \ (5.1) × 10^{-9}$} at 95% (90%) confidence level.